2012
DOI: 10.6090/jarq.46.81
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Green and Black Teas of Selected South India Cultivars

Abstract: Tea is one of the most popular global beverages. It is widely consumed as a health promoting beverage and its health benefits are mainly due to the presence of polyphenols such as catechins, theaflavins and thearubigins. The purpose of the present study is to evaluate the antioxidant potential of green tea (GT) and black tea (BT) extracts of eight different cultivars by radical scavenging activity (DPPH-RSA) and hydrophilic oxygen radical absorbance capacity (H-ORAC). The extracts of teas were also analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…More dramatic decrease was suffered in FFT samples which having the level DPPH scavenging activity only 6.08 ± 1.33%. The lessening result of DPPH scavenging activity due to tea fermentation was in agreement with recent investigation on DPPH scavenging activity of Camellia sinensis reported by Takano-Ishikawa et al (2012). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…More dramatic decrease was suffered in FFT samples which having the level DPPH scavenging activity only 6.08 ± 1.33%. The lessening result of DPPH scavenging activity due to tea fermentation was in agreement with recent investigation on DPPH scavenging activity of Camellia sinensis reported by Takano-Ishikawa et al (2012). …”
Section: Resultssupporting
confidence: 92%
“…There are several published reports about tea fermentation (Ariffin et al, 2011; Heong et al, 2011; Kim et al, 2011; Takano-Ishikawa et al, 2012; Xu et al, 2011), but most of them are focused on flavonoids content. Besides, those published reports on tea fermentation are used the common popular tea plants which are Camellia sinensis and Centella asiatica .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bupleurum rotundifolium extract revealed to have a weak ROS scavenging activity: 1277 µmol TE/g for the ORAC assay and 198 µmol TE per gram of dry extract for the DPPH assay. By comparison, previous studies with similar methods found that the ORAC values of green teas, which are often used as references, can range from 2730 to 5031 µmol TE/g and DPPH values from 1098 to 1376 µmol TE/g [16]. These results are not surprising when considering the low phenolic content, especially flavonoids [17].…”
Section: Discussionmentioning
confidence: 55%